2017
DOI: 10.1371/journal.pone.0172535
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of wrist-worn Fitbit Flex and waist-worn ActiGraph for measuring steps in free-living adults

Abstract: IntroductionAccelerometers are commonly used to assess physical activity. Consumer activity trackers have become increasingly popular today, such as the Fitbit. This study aimed to compare the average number of steps per day using the wrist-worn Fitbit Flex and waist-worn ActiGraph (wGT3X-BT) in free-living conditions.Methods104 adult participants (n = 35 males; n = 69 females) were asked to wear a Fitbit Flex and an ActiGraph concurrently for 7 days. Daily step counts were used to classify inactive (<10,000 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
75
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 42 publications
13
75
1
Order By: Relevance
“…We found that the monitor worn on the wrist detected a higher number of steps and activity counts as well as more percentage of time in physical activity and more percentage of time walking at moderate speed (1.05–1.3 m/s) when compared with the monitor worn on the waist. Similar results have been found in adults in the general population, where higher step counts have been reported from devices worn on the wrist when compared with the waist . Notably, studies with younger adults have reported smaller differences in the step count (median age 31 years, step difference 1381/median age 27 years, step difference 2558) when compared with the present study (mean age 68 years, step difference 3912) and a study conducted with older participants (mean age 72 years, step difference 4729).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that the monitor worn on the wrist detected a higher number of steps and activity counts as well as more percentage of time in physical activity and more percentage of time walking at moderate speed (1.05–1.3 m/s) when compared with the monitor worn on the waist. Similar results have been found in adults in the general population, where higher step counts have been reported from devices worn on the wrist when compared with the waist . Notably, studies with younger adults have reported smaller differences in the step count (median age 31 years, step difference 1381/median age 27 years, step difference 2558) when compared with the present study (mean age 68 years, step difference 3912) and a study conducted with older participants (mean age 72 years, step difference 4729).…”
Section: Discussionsupporting
confidence: 88%
“…Similar results have been found in adults in the general population, where higher step counts have been reported from devices worn on the wrist when compared with the waist . Notably, studies with younger adults have reported smaller differences in the step count (median age 31 years, step difference 1381/median age 27 years, step difference 2558) when compared with the present study (mean age 68 years, step difference 3912) and a study conducted with older participants (mean age 72 years, step difference 4729). The reason for this increase in difference in older people is unclear and may be the result of age‐related factors, including increased sedentary time producing more activity at the wrist compared with the waist.…”
Section: Discussionsupporting
confidence: 88%
“…One potential confounder includes the wrist versus waist location of the monitoring devices during data collection, although this arrangement is consistent with that of similar studies that compared data from these devices (2)(3)(4)10,(13)(14)(15)(16). The study could not control for wear time of the consumer devices, and this might have impacted results.…”
Section: Discussionmentioning
confidence: 63%
“…Fitbit, for example, an extremely popular fitness tracker, has been found to have low percent error compared with reference methods for energy expenditure estimation and step counting in some studies [39,45,46,47], but could be more biased in others [40]. …”
Section: Exposure Parameters and Sensorsmentioning
confidence: 99%